Intensity-Modulated Radiotherapy and Three-Dimensional Conformal Radiotherapy Combined with Intracavitary Posterior Radiotherapy for the Treatment of Medium-Term and Advanced Cervical Cancer: Efficacy, Safety and Prognostic Factors - Yu, Kewen; Zhou, Liping (Frontiers in Surgery, 2022)
Objective To explore the efficacy, safety, and prognostic factors of IMRT and 3D-CRT combined with intracavitary posterior radiotherapy for medium-term and advanced cervical cancer. Methods Retrospectively analyze the clinical data of 104 patients with medium-term and advanced cervical cancer who were treated in the radiotherapy department of our hospital from September 2015 to March 2017. According to the different radiotherapy techniques, they were divided into the IMRT combined with intracavitary posterior radiotherapy group (n=52) and the 3D-CRT combined with intracavitary posterior radiotherapy group (n=52). Observe and compare the short-term efficacy, occurrence of adverse reactions and overall survival rate of the two groups. The clinicopathological characteristics of the survival group and the death group were compared, and univariate analysis and multiple logistic regression models were used to analyze the relationship between the clinicopathological characteristics and the patient's prognosis. Results The total effective rate of IMRT combined with intracavitary posterior radiotherapy group was 96.15%, which was higher than that of 3D-CRT combined with intracavitary posterior radiotherapy group (88.46%), but the difference was not statistically significant (P>0.05). The incidence of digestive system injury, thrombocytopenia, and radiation proctitis in the IMRT combined intracavitary posterior radiotherapy group was lower than that of the 3D-CRT combined intracavitary posterior radiotherapy group, and the differences were statistically significant (P<0.05). The prognosis and survival of the two groups of patients were similar, and the difference was not statistically significant (P>0.05). Pathological classification, clinical stage, and lymph node metastasis are independent influencing factors of 3-year prognosis in patients with medium-term and advanced cervical cancer (P<0.05). Conclusion IMRT combined with intracavitary posterior radiotherapy is equivalent to 3D-CRT combined with intracavitary posterior radiotherapy, but it can reduce the incidence of adverse reactions in patients with medium-term and advanced cervical cancer, and has higher safety. Pathological typing, clinical staging, Lymph node metastasis were independent factor affecting the prognosis of patients. In clinical treatment, IMRT combined with intracavitary posterior radiotherapy is more recommended as a treatment plan for patients with medium-term and advanced cervical cancer.